Socialinės atsakomybės komunikcija Lietuvos organizacijų interneto svetainėse - Matkevičienė, Renata (Information & Media, 2013)
Nuo šio šimtmečio pradžios socialinės atsakomybės tema yra viena jautriausių tiek komunikacijos, tiek verslo srityse: įmonių vadovai, politikai, ekonomistai, mokslininkai svarsto socialinės atsakomybės veiklos apibrėžtis, teikiamą naudą verslui ar visuomenei. Diskusijose galima pastebėti kelis socialinės atsakomybės veiklos svarstymo aspektus: mados (atsakomybė visuomet buvo viena iš verslo siekiamybių ir veiklos pagrindų, todėl jos išryškinimas gali būti siejamas su tam tikra mada), būtinybės (kuri gali kilti dėl kitų verslo organizacijų aktyvios socialinės atsakomybės veiklos arba dėl visuomenės diktuojamo atitinkamos veiklos poreikio), galimi ir kiti požiūriai. Socialinės atsakomybės svarstymuose dažnai iškyla klausimas apie socialinės atsakomybės naudą verslui, apie apskaičiuojamą galimą socialinės atsakomybės grąžą verslui, kuriamą teigiamą įvaizdį ar reputaciją. Verslo organizacijos, siekdamos komunikuoti vykdomą socialiai atsakingą veiklą, tam pasitelkia įvairius renginius, ataskaitas, o dažniausiai – interneto svetaines. Šiame straipsnyje aptarsime ne tik anksčiau įvardytus diskusinius socialinės atsakomybės veiklos aspektus, bet ir ištirsime bei nusakysime galimus verslo organizacijų socialinės atsakomybės komunikacijos aspektus, išryškindami esmines akcentuojamas socialinės atsakomybės sritis. Straipsniu siekiama ne tik paskatinti kritinę diskusiją apie socialinės atsakomybės naudą ir būtinybę verslo organizacijų veikloje ir komunikacijoje, bet ir pažiūrėti, kaip socialinės atsakomybės veikla atsispindi organizacijų interneto svetainėse, su kokiais verslo ar organizacijos veiklos aspektais siejamas socialiai atsakingų veiklų pristatymas. Straipsnio tikslas ir sprendžiama problema formuluojami remiantis 2012 m. lapkričio–gruodžio mėnesiais atlikto Lietuvos organizacijų, priklausančių Baltosios bangos iniciatyvai „Už skaidrų verslą“, interneto svetainių turinio, atskleidžiančio organizacijų pristatomą socialinę atsakomybę, tyrimo ir straipsnio autorės 2013 m. kovą–balandį atlikto tyrimo, kuris papildė ir praplėtė ankstesnį tyrimą, duomenimis.Reikšminiai žodžiai: socialinė atsakomybė, organizacijų komunikacijos procesas, organizacijų veiklos etika, interneto svetainės.Communication of corporate social responsibility in Lithuanian organizations’ websitesRenata MatkevičienėSummary Since the beginning of this century, social responsibility has been one of the most sensitive topics in both communication and business areas, and business leaders as well as politicians, economists, scientists consider the social responsibility activities of the benefits for business or the public. Business organizations communicate socially responsible activities by using a variety of communication events, reports, and mostly websites of business organizations. This article aims to discuss not only the aspects of social responsibility, but also to examine and describe the potential of social responsibility communication in business organizations, highlighting the key areas of social responsibility. The article is aimed not only to encourage a critical discussion about the benefits of social responsibility and the need for business organizations and communications, but also to see how the social responsibility of business is reflected in organizations’ websites and presented to stakeholders. Business organizations’ social responsibility is generally associated with the activities of the organization, which aims to act responsibly: in accordance with the law, creating comfortable working conditions for employees, ensuring profitability – in collaboration with colleagues and local community as well as providing services to clients. Socially responsible activities have been associated not only with responsible activities, but also with commitments harming the surrounding environment, taking into account that socially responsible activities are voluntary, i.e. based on an organization’s desire to be a responsible, honest, trustworthy member of society not because of business requirements, but also for the organization’s internal needs based on corporate culture. Social responsibility of a business organization not only strengthens it because it involves employees and other groups of stakeholders in the organization’s activities, but it also provides an added value to the organization as a competitive advantage. In the article, there were formulated several tasks for communicating organizations’ social responsibility: to provide information, to impact the value or behavioural change. For the communication of social responsibility, organizations use controlled and as well non-controlled communication, and these forms of communication should be integrated to reach the aim of communication. Organizations’ websites are a controlled communication means, but they could be important for providing explicit information about the organization’s socially responsible activities. For this reason, an investigation of communication in the websites of Lithuanian business organiations that have joined the initiative of transparent business was conducted. Organizations communicate their social responsibility by presenting codes of ethics, standards, and other formal commitments which show that the organization is a responsible member of society. There were found differences in the communication of social responsibility in Lithuanian (local) and in international organizations: international organizations provide not only statements on the social responsibility of an organization, but also codes of ethics, CSR reports, presentations and videos of the projects, etc. Organizations use one-sided communication for the presentation of social responsibility in their websites, and tools for two-sided communication were notes used in many of the websites for communicating social responsibility. On the basis of this finding, the presupposition that organizations use other forms and means for communicating social responsibility was made, because the social responsibility activities carried out by an organization not only show the organization’s responsibility, but also allow linking the organization with certain practices and values, create an added value by increasing the visibility of the organization as a responsible member of the local community, developing and enhancing the organization’s reputation and ensuring its competitive advantage.